The Effect Of Self Assessment System On Tax Receiving Hotels In Sumedang District - Neni Hajijah; Tita Kartika; Fanji Farman (Journal of Business, Accounting and Finance, 2019)
Hotel taxes are one of the largest sources of tax revenue levied on hotel services. Hotel tax revenue can be obtained continuously and can be developed optimally with the application of the self assessment system. Based on this, this study aims to determine how well the implementation of the self assessment system and hotel tax revenue as well as the effect of the self assessment system on hotel tax revenue in Sumedang Regency. This research was conducted with a quantitative research method approach. The sampling technique uses simple random sampling with a sample of 76 hotel taxpayers. Data collection techniques using questionnaires, observation and documentation. Data analysis of research using inferential statistics to answer the formulation of descriptive problems. The results showed that the implementation of the self assessment system and hotel tax revenues were very good. Correlation analysis results show that the self assessment system has a strong relationship with hotel tax revenue with a correlation coefficient of 62.1%. Based on a simple regression test of self assessment system has a positive and significant effect on hotel tax revenue as shown by the equation Y = 14.740 + 0.683X and tcount> ttable by showing an effect of 49.4% which is analyzed using the coefficient of determination analysis.